Islamic Televangelism: Controversy and Da'wah Contest in Television Media - Titi Antin; Siti Mupida (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Digital technology has had a significant impact on several aspects of human life, especially on religious aspects. The birth of this religious fragmentation encouraged the presence of new religious, contemporary preachers and new audiences who contribute to revitalizing the debate over religious symbols. This article proposes thinking around the aspects that led to the development of the debate and contestation surrounding da'wah within the context of Islamic televangelism. The method used in this study is a qualitative descriptive method utilizing field observations and direct interviews with one of the Ustaz on television. The results of this study indicate that da'wah programs that are broadcast through television media give birth to a religious authority that is built between preaching actors thanks to the Islamic televangelism media. The contestation regarding religious authority, which was obtained thanks to its popularity in the television media, gave birth to the figure of a religious entrepreneur. Islamic televangelism has also sparked various controversies through preaching on television media, such as reprimands from KPI and even among fellow scholars.